Roles of Infection Prevention and Control Nurses (IPCNs) in Preparing for Emerging Infectious Diseases - Erna Tsalatsatul Fitriyah; Meidiana Dwidiyanti; Luky Dwiantoro (Holistic Nursing and Health Science, 2018)
Background: Infectious diseases have become one of the world’s serious problems including in Indonesia. Infectious diseases can originate from the community and hospital environment. Health workers performing inappropriate medical procedures could also be a cause of transmission of infectious diseases. Infection prevention and control nurses (IPCNs) as the pioneers of prevention and infection control in hospitals have not optimally played their roles.   Purpose: This study aimed to explore the roles of IPCNs and their constraints in preparing for emerging infectious diseases. Methods: The present study employed a qualitative design with the hermeneutic phenomenological approach. The samples were seven IPCNs for the primary participants, and two Infection Prevention and Control Officers (IPCOs) and 13 Infection Prevention and Control Link Nurses (IPCLNs) as the triangulation participants. The data were collected using in-depth semi-structured interviews analyzed using a content analysis technique.   Results: The results identified two themes: (1) IPCNs played roles as clinical practitioners, activity coordinators, administrators, and educators, and (2) the roles of IPCNs had not been optimal due to the lack of support from the hospital management, insufficient infrastructure, weak monitoring and evaluation, and the unavailability of appropriate rewards and  punishment.Conclusion: The majority of participants in this study agreed that IPCNs had tried well to play their roles. However, various obstacles were encountered, which hindered the IPCNs in performing their roles.